2018
DOI: 10.1021/acsanm.8b00063
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Trimodal Contrast Agent for Acoustic and Magnetic Particle Imaging of Stem Cells

Abstract: Stem cell therapy has the potential to improve tissue remodeling and repair. For cardiac stem cell therapy, methods to improve the injection and tracking of stem cells may help to increase patient outcomes. Here we describe a multimodal approach that combines ultrasound imaging, photoacoustic imaging, and magnetic particle imaging (MPI). Ultrasound imaging offers real-time guidance, photoacoustic imaging offers enhanced contrast, and MPI offers high-contrast, deep-tissue imaging. This work was facilitated by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 78 publications
2
68
0
Order By: Relevance
“…For PTX‐MB, the depth of imaging is currently limited by the penetration of 680 nm light in tissue, but photoacoustics can be coupled with other modalities such as ultrasound or magnetic resonance to locate the drug delivery site . This is a powerful tool to monitor the location and concentration of drugs and determine whether they remain encapsulated in nanocarriers.…”
Section: Resultsmentioning
confidence: 99%
“…For PTX‐MB, the depth of imaging is currently limited by the penetration of 680 nm light in tissue, but photoacoustics can be coupled with other modalities such as ultrasound or magnetic resonance to locate the drug delivery site . This is a powerful tool to monitor the location and concentration of drugs and determine whether they remain encapsulated in nanocarriers.…”
Section: Resultsmentioning
confidence: 99%
“…Since these studies have used very small FOV’s for brain or liver (not whole mouse FOV), with each cell containing >100-fold iron content, these MRI studies do not allow a proper comparison for its sensitivity of MPI. Multi-modal MPI cell tracking agents are now also being developed, although at the cost of a lower sensitivity in the order of 1 million cells [29]. …”
Section: Spios As Mpi Tracersmentioning
confidence: 99%
“…Moreover, the neural implant work imaged stem cells over 87 days, a study which would not be possible with the clinical tracer modalities today due to the need for radioactively decaying tracers. These early studies on stem cell lines have sparked further interest in the field of MPI stem cell tracking, leading to work demonstrating that MPI can be used to image pancreatic islet transplants in mice and work developing new nanoparticle agents for multimodal imaging of stem cells, including via MPI 29,30 . These studies demonstrated up to 200-cell sensitivity, which is far more sensitive than other medical imaging modalities 31 .…”
Section: Cell Trackingmentioning
confidence: 99%